Airway wall thickening on CT: Relation to smoking status and severity of COPD. (January 2019) - Charbonnier, Jean-Paul; Pompe, Esther; Moore, Camille; Humphries, Stephen; van Ginneken, Bram; Make, Barry; Regan, Elizabeth; Crapo, James D.; van Rikxoort, Eva M.; Lynch, David A.; ,
Abstract: Airway wall thickening in cigarette smokers is thought to be a result of inflammatory changes and airway remodeling. This study investigates if CT-derived airway wall thickening associates to disease severity in smokers with and without COPD and if airway wall thickening is reversible by smoking cessation. We examined 2000 smokers and 46 never-smokers who returned for a 5-year follow-up visit in the COPDGene-study. Multivariable regression analyses were performed at visit 1 to associate airway wall thickness (expressed as Pi10) with percent predicted forced expiratory volume in 1 s (FEV1 %-predicted), 6-min walking distance (6MWD), and St. George Respiratory Questionnaire (SGRQ). Longitudinal analyses were performed to assess the effect of smoking cessation on Pi10 using linear mixed models. A higher Pi10 was significantly associated with worse FEV1 %-predicted, 6MWD, and SGRQ in all GOLD-stages. Longitudinal analyses showed that subjects that quit smoking significantly decreased in Pi10 (ΔPi10 = −0.18 mm, p < 0.001). Subjects that started smoking had a significant increase in Pi10 (ΔPi10 = 0.14 mm, p < 0.001). Pi10 is a clinically relevant biomarker of smoking-related airway injury in smokers with and without COPD. The change in Pi10 with change in smoking status suggests that it can quantify a reversible component of smoking-related airway inflammation. Graphical abstract: Image 1